Effect of Exercise Modality During Weight Loss on Bone Health in Older Adults With Obesity and Cardiovascular Disease or Metabolic Syndrome: A Randomized Controlled Trial. (7th August 2018) - Beavers, Kristen M; Walkup, Michael P; Weaver, Ashley A; Lenchik, Leon; Kritchevsky, Stephen B; Nicklas, Barbara J; Ambrosius, Walter T; Stitzel, Joel D; Register, Thomas C; Shapses, Sue A; Marsh, Anthony P; Rejeski, W Jack
ABSTRACT: The objective of this study was to determine the ability of either aerobic or resistance training to counter weight‐loss‐associated bone loss in older adults. There were 187 older adults (67 years, 70% women, 64% white) with obesity (BMI = 34.5 ± 3.7 kg/m 2 ) and cardiovascular disease and/or metabolic syndrome who were randomized to participate in an 18‐month, community‐based trial, with a follow‐up assessment at 30 months. Intervention arms included: weight loss alone (WL; 7% to 10% baseline weight), WL plus aerobic training (WL + AT), and WL plus resistance training (WL + RT), as well as DXA‐acquired total hip, femoral neck, and lumbar spine areal bone mineral density (aBMD), and trabecular bone score (TBS). Biomarkers of bone turnover (procollagen type 1 N‐terminal propeptide, C‐terminal telopeptide of type 1 collagen) were measured at baseline, 6, 18, and 30 (aBMD and TBS only) months. CT‐acquired hip and spine volumetric BMD (vBMD), cortical thickness, and bone strength were measured in a subset at baseline ( n  = 55) and 18 months. Total hip aBMD was reduced by 2% in all groups at 18 months, with a primary analysis showing no significant treatment effects for any DXA, biomarker, or CT outcome. After adjustment for WL and follow‐up at 30 months, secondary analyses revealed that total hip [−0.018 (−0.023 to −0.012) g/cm 2 versus −0.025 (−0.031 to −0.019) g/cm 2 ; p  = 0.05] and femoral neck [−0.01 (−0.009 to 0.008) g/cm 2 versus −0.011 (−0.020 to −0.002) g/cm 2 ; p  = 0.06] aBMD estimates were modestly attenuated in the WL + RT group compared with the WL group. Additionally, lumbar spine aBMD was increased in the WL [0.015 (0.007 to 0.024) g/cm 2 ] and the WL + RT [0.009 (0.000 to 0.017) g/cm 2 ] groups compared with the WL + AT [−0.003 (−0.012 to 0.005)g/cm 2 ] group; both p  ≤ 0.01. Community‐based exercise does not prevent bone loss during active WL in older adults; however, adding RT may help minimize long‐term hip bone loss. © 2018 American Society for Bone and Mineral Research.